CDC7 kinase promotes MRE11 fork processing, modulating fork speed and chromosomal breakage. (4th June 2020) - Rainey, Michael D; Quinlan, Aisling; Cazzaniga, Chiara; Mijic, Sofija; Martella, Oliviano; Krietsch, Jana; Göder, Anja; Lopes, Massimo; Santocanale, Corrado
Abstract: The CDC7 kinase is essential for the activation of DNA replication origins and has been implicated in the replication stress response. Using a highly specific chemical inhibitor and a chemical genetic approach, we now show that CDC7 activity is required to coordinate multiple MRE11‐dependent processes occurring at replication forks, independently from its role in origin firing. CDC7 localizes at replication forks and, similarly to MRE11, mediates active slowing of fork progression upon mild topoisomerase inhibition. Both proteins are also retained on stalled forks, where they promote fork processing and restart. Moreover, MRE11 phosphorylation and localization at replication factories are progressively lost upon CDC7 inhibition. Finally, CDC7 activity at reversed forks is required for their pathological MRE11‐dependent degradation in BRCA2‐deficient cells. Thus, upon replication interference CDC7 is a key regulator of fork progression, processing and integrity. These results highlight a dual role for CDC7 in replication, modulating both initiation and elongation steps of DNA synthesis, and identify a key intervention point for anticancer therapies exploiting replication interference. Synopsis: CDC7 kinase acts at paused forks where it coordinates MRE11‐dependent fork processing, contributing to fork restart and modulating fork speed. Upon prolonged arrest and compromised fork protection, CDC7 promotes fork degradation contributing to replication‐dependent chromosome breakage. CDC7 promotes fork restart, HU‐dependent fork collapse and chromosomal breakage. CDC7's role at forks can be uncoupled from its role in origin activation. MRE11 and CDC7 activities are required to limit fork progression upon mild topological stress. CDC7 promotes the degradation of reversed forks in BRCA2‐depleted cells. Abstract : CDC7 kinase acts at paused forks where it coordinates MRE11‐dependent fork processing, contributing to fork restart and modulating fork speed. Upon prolonged arrest and compromised fork protection, CDC7 promotes fork degradation contributing to replication‐dependent chromosome breakage.